HUBUNGAN SISA MAKANAN DAN ASUPAN ZAT GIZI MAKRO DENGAN STATUS GIZI REMAJA DI MADRASAH ALIYAH BALI BINA INSANI TABANAN - Made Chandra Nirmala Buana (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2023)
Madrasah Aliyah Bali Bina Insani is one of the educational institutions that conducts food delivery to meet the intake needs of their students. The results of preliminary observations to 20 students showed that no one said that the combination of food served by the hostel was interesting, which would lead to leftovers. This study generally aims to determine the correlation of food waste and macro nutrient intake with the nutritional status of adolescents in Madrasah Aliyah Bali Bina Insani Tabanan. This type of research is observational with crosssectional design. The number of samples in this study were 61 people. The results of the study found that the food waste data obtained the results that all samples (100%) had a little food waste. Then on the intake data, 72.1% had less energy intake, 73.8% had less protein intake, 73.8% had less fat intake, and 73.8% had less carbohydrate intake. In the nutritional status data, 3.3% have underweight nutritional status, 4.9% have over nutritional status, and 8.2% have obese nutritional status. Pearson correlation analysis results showed that there was no significant correlation between food waste with energy (p = 0.136), protein (p = 0.208), fat (p = 0.549), and carbohydrates (p = 0.706). While the Pearson correlation test between macro nutrient intake and nutritional status, it was found that there was a significant correlation between energy intake (p = 0.022), protein (p = 0.028), fat (p = 0.025), and carbohydrate (p = 0.034) with adolescent nutritional status. The hostel is expected to be able to reduce food waste by paying attention to variations in menus and serving food provided to students in order to meet the nutritional needs of students. Keyword : nutritional status, food waste, macronutrient intake